2009
DOI: 10.1007/bf03191380
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of hydroxy metabolites of clarithromycin to the pharmacokinetic parameters, and determination of hydroxy metabolites ratio of clarithromycin

Abstract: Clarithromycin is a broad-spectrum macrolide antibacterial agent which is effective both in vitro and in vivo against the major pathogens responsible for respiratory tract infections. Clarithromycin's principal metabolite is 14-(R) hydroxyclarithromycin (14-OH-clarithromycin). The other metabolite, namely 14-(S) hydroxyclarithromycin is inactive. The purpose of this study was to show the hydroxylation of CLA at the 14 position to form the R and S epimers and to determine the metabolic ratio of 14ROHCLA/CLA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Около 60% эритромицина экскретируется с желчью и около 40% -с мочой, основным метаболитом является N-дезметилэритромицин [3]. Кларитромицин также интенсивно (на 78%) [28] метаболизируется в печени путём окислительного N-деметилирования и гидроксилирования при участии изоферментов CYP3A4, CYP3A5 и CYP3A7 до неактивного метаболита N-дезметилкларитромицина и активного метаболита 14-(R)-гидроксикларитромицина [29,30]. Кларитромицин на 20-30% выводится почками в неизменённом виде и на 10-15% -в виде метаболитов [28].…”
Section: Discussionunclassified
“…Около 60% эритромицина экскретируется с желчью и около 40% -с мочой, основным метаболитом является N-дезметилэритромицин [3]. Кларитромицин также интенсивно (на 78%) [28] метаболизируется в печени путём окислительного N-деметилирования и гидроксилирования при участии изоферментов CYP3A4, CYP3A5 и CYP3A7 до неактивного метаболита N-дезметилкларитромицина и активного метаболита 14-(R)-гидроксикларитромицина [29,30]. Кларитромицин на 20-30% выводится почками в неизменённом виде и на 10-15% -в виде метаболитов [28].…”
Section: Discussionunclassified
“…However, researchers have suggested that the active metabolite of clarithromycin, 14-hydroxy-clarithromycin (14-HC), can act synergistically both in vitro and in vivo with its parent molecule, enhancing the anti- Haemophilus activity of the macrolide 39,6671. Using in vitro checkerboard and kill-curve bactericidal assays, Bergeron et al69 and Hoover et al70 were able to demonstrate synergy between clarithromycin and 14-HC against some strains of Haemophilus , as well as Enterococcus and Staphylococci .…”
Section: Introductionmentioning
confidence: 99%